Disco - Trantraal, Nathan (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2020)
Creative writing portfolio.
Keywords: Kaaps; South African fiction (English) -- 21st century; South African poetry (English) -- 21st century; Afrikaans fiction -- 21st century; Afrikaans poetry -- 21st century